Effects of Dried Distillers’ Grain on Fecal Prevalence and Growth of Escherichia coli O157 in Batch Culture Fermentations from Cattle - Jacob, M. E.; Fox, J. Trent; Drouillard, James S.; Renter, David G.; Nagaraja, Tiruvoor G. (My University, 2008)
Distillers’ grains (DG), a by-product of ethanol production, are fed to cattle. Associations between Escherichia coli O157 prevalence and feeding of DG were investigated in feedlot cattle (n = 379) given one of three diets: steam-flaked corn (SFC) and 15% corn silage with 0 or 25% dried distillers’ grains (DDG) or SFC with 5% corn silage and 25% DDG. Ten fecal samples were collected from each pen weekly for 12 weeks to isolate E. coli O157. Cattle fed 25% DDG with 5 or 15% silage had a higher (P = 0.01) prevalence of E. coli O157 than cattle fed a diet without DDG. Batch culture ruminal or fecal microbial fermentations were conducted to evaluate the effect of DDG on E. coli O157 growth. The first study utilized microbial inocula from steers fed SFC or dry-rolled corn with 0 or 25% DDG and included their diet as the substrate. Ruminal microbial fermentations from steers fed DDG had higher E. coli O157 contents than ruminal microbial fermentations from steers fed no DDG (P < 0.05) when no substrate was included. Fecal fermentations showed no DDG effect on E. coli O157 growth. In the second study with DDG as a substrate, ruminal fermentations with 0.5 g DDG had higher (P < 0.01) E. coli O157 concentrations at 24 h than ruminal fermentations with 0, 1, or 2 g DDG. In fecal fermentations, 2 g DDG resulted in a higher concentration (P < 0.05) at 24 h than 0, 0.5, or 1 g DDG. The results indicate that there is a positive association between DDG and E. coli O157 in cattle, and the findings should have important ramifications for food safety.